Hermeneutika Manhaj Tafsir Fazlur Rahman - Abu Yazid Adnan Quthny; Abd Hannan (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2019)
As a method of Tafsir - in the context of classical science -, hermeneutics is used to solve, interpret and interpret the meanings contained in scriptures, jurisprudence, ancient documents and texts. Hermeneutics as a theory of interpretation will surely give birth to hetereutic products as operational-applications tafsirnya. Fazlur Rahman is one of contemporary Muslim thinkers using the hermeneutic approach in nash interpretation. He grew up in a strong family environment in holding religious teachings by adopting a system of schools against Imam Hanafi (Sunni) as a figure of mujtahid madhhab ulama with traditional-conventional Islamic thinking and developing his scholarship to Western world which influenced many modern-contemporary thinking patterns. Rahman's education with traditional and contemporary background is apparent in his ijtihad results by carrying on the Qur'an, systematic-interpretation and logical-synthesis approaches. Rahman's traditional-liberal form of thought can be understood from his superior theory of double movement theory which was launched in 1982 AD with his basic ideas and ideas about the fundamental differences between the legal aspects of the Qur'an and the ideal aspects of the moral al -Qur'an. The integration of an education system of the traditional system in the state of origin (Pakistan) with the modern system of philosophy while continuing its studies in the West (France) made Rahman consistent with the position of al-Qur'an and sunna as the source of the first and main Islamic teachings as a means to uncover the meaning of the text and messages of both mashdar al-hukm. Fazlur Rahman classified as a unique and prominent thinker of his time is very interesting to be studied. He grew up in Pakistan and expanded his science to France and then to Chicago Canada who was later invited by his local government to return to help in Pakistan. But his struggle in his birthplace did not last long which made Rahman have to move back to Chicago, Canada. It seems like this hijrah experience as a reference to make it easier to remind us of the popular hermeneutic theory which is also pacing or reciprocity between inductive and deductive ie double movement theory around text, context and contextualization Keywords: method , Tafsir and hermeneutics